Media as a Political Tool: Comparative Study Between Indonesia and Saudi Arabia - Khalid Vikriadi; Ainiyatul Latifah; Riky Ovaliansyah Harahap; Tiara Ramadhani; Aubaidillah Doloh; Nurul Kamaly (Winaya Inspirasi Nusantara Foundation, 2026)
While media freedom is traditionally framed within a democracy-authoritarianism dichotomy, emerging patterns of digital control suggest that state-media interactions are becoming increasingly complex. This study addresses the background problem of how varied political regimes in Muslim-majority nations instrumentalize media to maintain legitimacy and manage public discourse. The primary research objective is to develop a cross-regime typology by comparing media control mechanisms in Indonesia, an electoral democracy, and Saudi Arabia, an absolute monarchy. Utilizing a qualitative comparative case study design, the methodology involves the thematic analysis of official legal frameworks, international press freedom reports, and digital archive data from 2019 to 2025. The key findings reveal that Indonesia employs